2013
DOI: 10.1155/2013/873939
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Adherence to Antiretroviral Therapy among HIV/AIDS Patients in the Upper West Region of Ghana

Abstract: Background. The effectiveness of ART interventions is only realized in maximal levels of adherence. A near perfect adherence level of >95% is required for the effective suppression of HIV/AIDS virus. The main objective of this study was to identify the sociodemographic and socioeconomic factors that facilitate adherence to antiretroviral therapy among HIV/AIDS patients. Methods. This descriptive cross-sectional study was conducted between March and May 2013 at the Upper West Regional Hospital, Wa. A total of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
71
3
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(86 citation statements)
references
References 8 publications
9
71
3
3
Order By: Relevance
“…The relationship between perceived benefit and barrier and ARV therapy adherence The result of the study showed that there was a relationship between perceived benefit and barrier and the compliance to ARV therapy which was statistically significant with the score of (p= 0.016), high perceived benefit and barrier would increase the compliance to conduct ARV therapy. These results supported the research of Obirikorang et al (2013) which stated that other diseases and drug side effects negatively affected the adherence of ARV therapy while the perceptions of health, family support and regularity have a positive effect on ARV therapy.…”
Section: The Relationship Between Know-supporting
confidence: 88%
“…The relationship between perceived benefit and barrier and ARV therapy adherence The result of the study showed that there was a relationship between perceived benefit and barrier and the compliance to ARV therapy which was statistically significant with the score of (p= 0.016), high perceived benefit and barrier would increase the compliance to conduct ARV therapy. These results supported the research of Obirikorang et al (2013) which stated that other diseases and drug side effects negatively affected the adherence of ARV therapy while the perceptions of health, family support and regularity have a positive effect on ARV therapy.…”
Section: The Relationship Between Know-supporting
confidence: 88%
“…The finding is in consonance with other studies. 6,12 Majority of patients (84.31%) were on non PI based regime. This finding is in accordance with other studies.…”
Section: Resultsmentioning
confidence: 99%
“…This low level of non-adherence to ART highlights the success of the national ART program in Kenya, where non-adherence levels are lower than reported in other sub-Saharan African countries, including: Rwanda, where 23% of ART patients were non-adherent based on 30-day recall [14]; Ghana, where 14% of ART patients were non-adherent [15]; rural Zambia where 40% of ART patients were not adherent [16], and a pooled analysis of African adherence studies, where overall non-adherence levels were reported to be 23% [17]. Data from developed countries also suggest higher non-adherence levels, with estimates of 45% in a pooled analysis of adherence studies in North America [17], 37% in Sweden [18], 34% in Brazil [19], and 43% in Spain [20].…”
Section: Discussionmentioning
confidence: 99%